Chemical zoning and microtexture of magnetite from Los Colorados iron oxide-apatite deposit, Chile - Reich, Martín; Simon, Adam C; Deditius, Artur; Bilenker, Laura; Knipping, Jaayke; Barra-Pantoja, Luis Fernando (2019)
The Cretaceous Chilean Iron Belt comprises more than 40 iron oxide-apatite (IOA) "Kiruna-type" deposits that extend ~600 km along the Coastal Range of northen Chile and occur within the domain of the southernmost segment of the sinistral strike-slip Ataca FONDECYT FONDECYT